On three types of sea breeze in Qingdao of East China: an observational analysis - Guo, Zihan; Cao, Lijuan; Guo, Jianping; Shang, Mengjiao; Guo, Xiaoran (Frontiers in Environmental Science, 2023)
Our knowledge of sea breeze remains poor in the coastal area of East China, due largely to the high terrain heterogeneity. Five–year (2016–2020) consecutive wind observations from a 10–m wind tower and radar wind profiler are used to characterize the sea–land breeze at Qingdao, a coastal city in East China. The sea surface temperatures at the nearby buoy station in the Yellow Sea are further used to elucidate the land–sea thermal contrast. First of all, three types of sea breeze are determined according to the temporal evolution of wind direction, including pure sea breeze (PSB), corkscrew sea breeze (CSB) and backdoor sea breeze (BSB). Statistically, there are 522 days experiencing sea breezes, of which 61 days belong to PSB, 40 days witness CSB, and only 2 days see the BSB. The occurrence of sea breeze is found to peak from April to September and the average wind speed lies at 3–5 m s-1. This suggests a salient seasonality of sea breeze at Qingdao, which is likely caused by the seasonal dependence of land–sea thermal contrast. In terms of the diurnal variability, the sea breezes tend to occur more frequently and have more intensity in the afternoon compared with in the morning, irrespective of sea breeze types. Interestingly, the BSB is merely observed in autumn, whereas CSB and PSB can be found year round. Among all types of sea breeze, the PSB has the highest intensity and most frequency throughout the daytime, same in the seasons of spring, summer and autumn. Further analyses are conduced of the synoptic pattern, lower troposphere stability (LTS) and bulk Richard number (Ri) for three types of sea breeze. Both PSB and CSB in Qingdao are characterized by prevailing westerlies at 500 hPa. In contrast, the BSB is generally accompanied with easterlies at 850 hPa. Meanwhile, the BSB has the lowest LTS, in sharp contrast to the highest LTS for the PSB. This indicates that the BSB (PSB) tends to occur in an unstable (stable) lower troposphere. The findings obtained here highlight the importance of typing sea breeze.